Effects of solar radiation and tree planting on photochemical reaction kinetics in urban street canyon - Wang, Ke-Xin; Cui, Peng-Yi; Huang, Yuan-Dong; Luo, Yang; Feng, Jun-Jie; Wang, Jin-Long; Xing, Gang-Yi (Applied thermal engineering, 2024)
By coupling the dynamic and thermodynamic effects, the planting trees in street canyon can enhance the ventilation capacity, reduce the air temperature and affect the equilibrium process of NOx-O3 photochemical reaction and promote its reverse reaction to ozone depletion. [Display omitted] •The coupled effects of tree greening and solar radiation on NOx-O3 photochemical reaction are investigated.•Different local solar times (LST) and background ozone concentrations [O3]b are considered.•Ozone depletion rate (dO3) is specified to evaluate the photochemical reaction equilibrium.•Planting trees can enhance the ventilation capacity and reduce the air temperature effectively.•Planting trees can affect the NOx-O3 reaction equilibrium and promote its reverse reaction to O3 depletion. The investigation of the impact of tree planting on photochemical reaction kinetics and dispersion characteristics of reactive pollutants in street canyons under actual solar radiation remains a pertinent subject for research. The numerical models were employed and validated through wind-tunnel experiments to investigate the dynamic and thermodynamic effects of tree planting (LAD = 4.77) on turbulent flow, heat transfer, and NOx-O3 photochemical reaction in urban street canyons. The effects of solar radiation at three local solar times (LST0900, LST1200 and LST1500) and three background O3 concentrations (20 ppb, 100 ppb and 200 ppb) were considered. The ozone depletion rate (dO3) was defined to measure the photochemical reaction equilibrium. The results show that the presence of trees can offset the impact of varying LST solar radiation and promote greater stability in flow structures within street canyons. Specifically, a stable clockwise main vortex is observed in the upper part, while multiple smaller vortices form more regularly in the lower part. Compared with no trees, planting trees can effectively reduce the temperature by about 5 K in the lower part of street canyon through the shading and transpiration cooling effects. In conjunction with its dynamic effects, the tree planting can also effectively reduce the average concentration of pollutants before the reaction. It results in a predominant accumulation of NOx near the pollution source at the bottom center, thereby mitigating their detrimental impacts on both windward and leeward sides. Additionally, under the same background O3 concentration, tree planting can also influence the equilibrium process of photochemical reactions and enhance their reverse reaction leading to ozone depletion. The findings of this study contribute to a deeper understanding of the impact of tree greening on the local microclimate within urban street canyons.